Associaton between Blood Total Testosterone Levels and Consolidated Memory on Eldery Men at Veterans Institution - Muhammad Hamdan1 , Raini Wisnujono1 , Yudha Haryono1 , Abdulloh Machin2 , Euginia Putri Permata P.2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Decreased total testosterone levels in the blood will disrupt memory consolidation. In this phase, one could still function normally even though it is difficult to recall the information that has been learned. Methods: The subjects were taken consecutively and conducted by interview, generalist, and neurological physical examination, Word List Memory Task examination twice as well as measurement of total testosterone in the blood. The subjects were grouped into total blood testosterone levels of less than 298 ng/ dl and more than equal to 298 ng/dl. Results: Fifty-four subjects studied obtained that total blood testosterone levels <298 ng/dl in the Word List Memory Task (WLMT) group <21 (62.5%) were higher than the WLMT group ?21 (37.5%). Furthermore, Total Testosterone in the blood more ?298 ng/dl in the WLMT group <21 (15.2%) was less than in the WLMT group ?21 (84.8%). Conclusion: There was a correlation between total testosterone levels in the blood and memory consolidation in elderly men at the Veterans’ Institute of Republic Indonesia in Surabaya.